Medical and surgical management has a role in control of intraocular pressure in early detected iridocorneal endothelial syndrome: case series - Rath, Archana; Mohapatra, Sumita; Betdur, Rakesh A.; V. K., Harshvardhan (International Journal of Advances in Medicine, 2017)
Iridocorneal endothelial syndrome is a rare ocular disorder characterized by abnormal endothelization of angle structure and iris producing characteristic manifestation including secondary angle closure glaucoma. The purpose is to present four cases of iridocorneal endothelial syndrome with glaucoma and discuss clinical presentation and management strategies. Out of four cases, two cases of Cogan-Reese syndrome who present early have well controlled IOP with trabeculectomy with mitomycin-C. One case who presented late with progressive iris atrophy and secondary angle closure glaucoma went to absolute stage in spite of trabeculectomy with mitomycin-C. One case with Chandler’s syndrome has well controlled IOP with topical anti-glaucoma medication.